The Effect Of Feeding Modification On Changes In The Troponin Level Of Heart Patients In Aster Inpatient Ward Of Dr. Moewardi Regional General Hospital Surakarta - Farudin, Ahmad; Sari, Anita Wulan; Fauzia, Marliana Tiwi (Indonesian Basic and Experimental Health Sciences, 2024)
Background: The heart is an organ that pump blood to the entire body system and draw the blood back into the heart. The inability of the heart to perform its functions is generated by damage to the anatomy or physiology of the heart, which induces various diseases of the cardiovascular system. Cardiovascular disease is the leading cause of death in the world. (Dewanti, I.P, 2014). One in ten deaths in the world is caused by heart disease. This makes heart attacks the leading cause of death in the world every year. One of the criteria for Infarc Myocard Acute (IMA)  diagnosis by World Health Organization (WHO) is an increase in heart enzyme levels. Troponin is one of the heart enzymes that will increase if there is a myocardial cell damage. A study conducted at West Sumatra Main Branch of YJI Heart Specialist Hospital in the period of July 2013 – June 2014, discovered 81 patient data with IMA diagnosis and 37 data with Troponin and ECG examination results. (Primananda, M.L, Syafri, M, and Meinapuri, 2014) Dr. Moewardi Regional General Hospital is one of the hospitals in Surakarta City that has specialized wards for patients with heart disease, one of which is the Aster room. Food intake in heart patients is part of the therapy given. The dietary intake of heart patients treated at Dr. Moewardi Hospital is still below 80% of the target quality of the Nutrition Installation. Low food intake can be instigated by low appetite, a feeling of abdominal bloating. Small frequent feeding portions is one way to increase the feeding intake of heart patients. Based on these circumstances, it is necessary to conduct a study to determine the effect of feeding modification and eating frequency on nutrient intake and changes in troponin level of heart patients in the Aster Ward of Dr. Moewardi Regional General Hospital Surakarta. Purpose of the Study: discovering the description of the effect of feeding modification on changes in troponin level of heart patients in Aster inpatient ward of Dr. Moewardi Regional General Hospital. Method of the Study: It was an analytical description study the study design used in this study was "One Group Pretest-Posttest Design", which is a study design that contains pretest before treatment and posttest after treatment. Thus, it can be more accurately discovered, since it compares the result before and after the treatment is applied Result: The troponin level before the administration of High Protein Low Fat (HPLF) diet was higher compared to the troponin level of respondents who obtained HPLF diet. The highest Pre- and post-treatment troponin levels were > 40,000 ng/mL, while the lowest pre-treatment troponin level was 18 ng/mL, and the lowest post-treatment level was 10 ng/ml. The average difference in troponin levels was the average decrease in pre- and post-troponin tests of 1895.7 ng/ml. Conclusion: The description of the effect of feeding modification on changes in troponin level of heart patients in Aster inpatient ward of Dr. Moewardi Regional General Hospital is as follows: (a) The number of samples in this study is 21 respondents, with 17 men and 4 women. (b) The highest energy intake value of pre-treatment is 1638 calories, the highest intake on the first day of post-treatment is 1845 calories, while on the second day of post-treatment is 1843 calories (c) There is an average decrease in troponin level post-treatment of feeding modification of 1895.7 ng/ml.